Dry eye disease and its treatment in women over 45 years - E.A. Drozdova; V.E. Balan (РМЖ "Клиническая офтальмология")
E.A. Drozdova1, V.E. Balan2 1South Ural State Medical University, Chelyabinsk, Russian Federation 2Moscow Regional Research Institute of Obstetrics & Gynecology, Moscow,   Russian Federation Epidemiological studies demonstrate an increase in age-related prevalence of dry eye disease (DED) and its higher occurrence in women. In addition to age-related alterations of structures producing tear film, the reduction of androgen levels and other regulating hormones is important for DED development. The role of estrogens and progesterone in the regulation of lacrimal and meibomian gland activity is still disputable. Additional factors of DED development in women are a high rate of comorbidities affecting gland functions, use of cosmetics and cosmetic procedures, contact lens wearing. The results are partial atrophy of meibomian glands, changes in the quality and amount of their secret, increased tear evaporation. Cationic nano-emulsion that addresses the deficiency and stabilize the lipid layer, increases water content, and reduces tear osmolarity is recommended for DED in women. Keywords: dry eye disease, tear film, meibomian glands, postmenopausal, lipid layer, tear  osmolarity, artificial tears, cationic nano-emulsion. For citation: Drozdova E.A., Balan V.E. Dry eye disease and its treatment in women over 45 years. Russian Journal of Clinical Ophthalmology. 2021;21(2):–107. DOI: 10.32364/2311-7729-2021-21-2-103-107.